Colonização pelo streptococcus do grupo b: prevalência, fatores de risco, características fenotípicas e genotípicas, em mulheres no terceiro trimestre de gestação, atendidas por serviço de referência materno infantil de Goiânia-Goiás - Pires, Telma Sousa (2009)
To estimate the prevalence, to asses risk factors for Group B Streptococcus (GBS) colonization and to describe phenotypic and genotypic characteristics of isolated strains from pregnant women in Goiânia, Goiás. Methods: A cross sectional study was carried out among 198 pregnant women, at least at the 32o weeks´ gestation, attending a reference health unit, from March to June 2009. Socio, demographic and obstetric profiles were investigated using a standard questionnaire. Samples of vaginal and rectal secretion were collected and placed into selective enrichment broth Todd-Hewitt. Tests for GBS identification (gram, catalase and CAMP) followed by susceptibility test using antibiotic disk diffusion technique were performed. Genetic diversity was assessed by pulsed-field gel electrophoresis (PFGE). Descriptive and analytic statistical tests were applied (Epi Info e SPSS 13.0). Analyses were performed at the Instituto de Patologia Tropical Saúde Pública/UFG. Results: Thirty pregnant women were colonized by GBS yielding a prevalence of 15.2% (IC95% 10.5 ?? 20.9). Pregnant women younger than 20 years and with low income had higher risk of GBS colonization, in univariate analysis (p<0.05). GBS was isolated from 28 vaginal and 14 rectal specimens. Twelve pregnant were vaginal and rectal colonized. All 42 strains were susceptible to penicillin, vancomycin, ceftriaxone and levofloxacin. Three strains (7.1%) were resistant to erythromycin and two (4.7%) to clindamycin. 19 pulsotypes and four clusters were identified. Nine out 12 pars of positive strains (vaginal and rectal) were genetically identical, two were stricted related and one par was colonized by different strains. The same genetic profile was observed in more than one pregnant. Conclusions: Socioeconomic and obstetrics variables had low predictive value for GBE colonization among pregnant women, reinforcing the need for universal microbiology screening strategy in this population, in order to prevent neonatal sepsis. A high genetic diversity of GBS was found among pregnant women in Goiania.